Abrogating Native α-Synuclein Tetramers in Mice Causes a L-DOPA-Responsive Motor Syndrome Closely Resembling Parkinson's Disease - Nuber, Silke; Rajsombath, Molly; Minakaki, Georgia; Winkler, Jürgen; Müller, Christian P.; Ericsson, Maria; Caldarone, Barbara; Dettmer, Ulf; Selkoe, Dennis J. (Neuron, 2018)
α-Synuclein (αS) regulates vesicle exocytosis but forms insoluble deposits in Parkinson's disease (PD). Developing disease-modifying therapies requires animal models that reproduce cardinal features of PD. We recently described a previously unrecognized physiological form of αS, α-helical tetramers, and showed that familial PD-causing missense mutations shift tetramers to aggregation-prone monomers. Here, we generated mice expressing the fPD E46K mutation plus 2 homologous E→K mutations in adjacent KTKEGV motifs. This tetramer-abrogating mutant causes phenotypes similar to PD. αS monomers accumulate at membranes and form vesicle-rich inclusions. αS becomes insoluble, proteinase K-resistant, Ser129-phosphorylated, and C-terminally truncated, as in PD. These changes affect regions controlling motor behavior, including a decrease in nigrostriatal dopaminergic neurons. The outcome is a progressive motor syndrome including tremor and gait and limb deficits partially responsive to L-DOPA. This fully penetrant phenotype indicates that tetramers are required for normal αS homeostasis and that chronically shifting tetramers to monomers may result in PD, with attendant therapeutic implications.
EVALuna2:36380